2021
DOI: 10.3390/biomedicines9101308
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Sestrin2 in Alzheimer’s Disease: Antioxidation, Autophagy Promotion, and Beyond

Abstract: Alzheimer's disease (AD) is the most common age-related neurodegenerative disease. It presents with progressive memory loss, worsens cognitive functions to the point of disability, and causes heavy socioeconomic burdens to patients, their families, and society as a whole. The underlying pathogenic mechanisms of AD are complex and may involve excitotoxicity, excessive generation of reactive oxygen species (ROS), aberrant cell cycle reentry, impaired mitochondrial function, and DNA damage. Up to now, there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 148 publications
(227 reference statements)
0
2
0
Order By: Relevance
“…The exploration of Therapeutic strategies through mediation of Sestrin2 is now underway. Several natural products and medications in diabetes have been shown to alter the expression levels of Sestrin2, which lead to the possibility of novel treatments in diabetes and diabetic complications targeting Sestrin2 and the associated pathways ( 211 ). Initially, a few studies investigated the potential mediator of Sestrin2 in the field of tumor therapies, including several small molecules ( 212 ).…”
Section: Possible Pharmacological Mediators Of Sestrin2mentioning
confidence: 99%
“…The exploration of Therapeutic strategies through mediation of Sestrin2 is now underway. Several natural products and medications in diabetes have been shown to alter the expression levels of Sestrin2, which lead to the possibility of novel treatments in diabetes and diabetic complications targeting Sestrin2 and the associated pathways ( 211 ). Initially, a few studies investigated the potential mediator of Sestrin2 in the field of tumor therapies, including several small molecules ( 212 ).…”
Section: Possible Pharmacological Mediators Of Sestrin2mentioning
confidence: 99%
“…Sestrin-2, a pressure sensor protein, was found to have a neuroprotective effect by polarizing microglia cells in the ischemic mouse brain from the pro-inflammatory M1 to the anti-inflammatory M2 phenotype ( 32 ). By augmenting sestrin-2 expression in disease models, the function of neurons was enhanced, allowing them to cope with oxidative stress and thus adapt to stressful conditions ( 33 ). A previous study has shown that patients with primary insomnia had a reduced ability to resist oxidative stress ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some molecules, such as amarogentin, seem able to interact with this receptor, representing potential candidates for future clinical studies [4]. Other classes of newer drugs, such as SGLT-2 inhibitors [5] and sestrins [6], could be considered to reduce mTOR activity, acting after the insulin receptor cascade and slowing neurodegeneration. Sestrins seem able to also act in other commonly disrupted pathways in AD, such as, for example, by improving antioxidation and adjusting autophagy.…”
mentioning
confidence: 99%